Bridging Cultures: Collaborative Learning Between Malagasy Darmasiswa Scholar and English Education Student at UKI Toraja - Roni La'biran; Markus Deli Girik Allo; Judith Ratu Tangdiarrang; Elim Trika Sudarsi; Nilma Taula'bi; Resnita Dewi; Adrial Kala’lembang; Maminiaina Andosoa Faniriana (STAI Hubbulwathan Duri, 2025)
This study investigates the collaborative learning experiences between Malagasy Darmasiswa scholars and English Education students at Universitas Kristen Indonesia Toraja (UKI Toraja). The Darmasiswa program, initiated by the Indonesian government, facilitates cross-cultural academic exchange by offering scholarships to international students, including those from Madagascar. The research focuses on how these intercultural collaborations impact participants' language acquisition, communication skills, and educational development. Using qualitative methods, including semi-structured interviews and participant observation, data were collected from both Malagasy and Indonesian students engaged in joint learning activities. These activities encompassed intercultural workshops, language exchanges, and collaborative projects centered on cultural comparison and language practice. Preliminary findings indicate that collaborative learning fosters improved intercultural communication skills, increased language fluency, and greater cultural empathy. Both groups reported enhanced confidence in cross-cultural settings and a deeper understanding of each other’s cultural perspectives. The learning environment was described as more inclusive and mutually supportive. The findings underscore the educational value of structured intercultural collaboration. Participants not only developed stronger language and communication skills but also demonstrated increased cultural awareness and engagement. These outcomes suggest that such initiatives significantly contribute to the holistic academic growth of both international and local students. The study recommends enhancing collaborative learning by integrating structured intercultural components, expanding joint activities, and promoting ongoing peer engagement. These improvements could deepen intercultural understanding and further enrich the educational experience for all participants.